Perancangan dan Pengembangan Sistem Pengarsipan Surat Berbasis Web Menggunakan Metode Waterfall - Nirsal, Nirs; M, Rispayanti (Institut Teknologi Garut, 2025)
This study aims to create a website-based letter archiving information system at the Dangerakko Village Office. This application is expected to facilitate the process of managing letter archives at the Dangerakko Village Office. The type of research used in this study is Research & Development (R&D) using the Waterfall development method. The data collection methods used are observation, interviews, and literature study. The system model design uses the Unified Modeling Language (UML) approach, which consists of use case diagrams, activity diagrams, class diagrams, and sequence diagrams created using Draw.io. The interface design is created using Balsamiq. In the system development stage, the PHP programming language and the Bootstrap Framework are used to build the website. The program code was written using the Sublime Text application, and the database was created using MySQL from XAMPP. Google Chrome was used to view the system display. System testing used the black box method and system design testing was carried out by Dangerakko Village staff, as well as system usability testing using the System Usability Scale (SUS) method. The results of the black box testing showed that all buttons functioned properly. The system design testing, which included UML, interface, and database, scored 100%, while the usability testing (SUS) scored 84%, indicating it is highly suitable.